OPTIMALISASI HAFALAN AL-QUR'AN MELALUI METODE KAUNY QUANTUM MEMORY DI SANGGAR BELAJAR MUALLIM PERAK, MALAYSIA - Rakhman, Itmam Aulia; Khoirunnisa; Koidin, Mohammad; Zakiyah (DEVELOPMENT: Journal of Community Engagement, 2025)
This study aims to optimize Quran memorization through the implementation of the Kauny Quantum Memory (KQM) method at Sanggar Belajar Muallim in Perak, Malaysia, where the majority of participants are immigrant children with limited access to formal education. The KQM method was chosen due to its effectiveness in enhancing memorization efficiency, strengthening long-term memory retention, and integrating verse comprehension through engaging movements and a fun learning approach. Using a qualitative descriptive approach, this research employed observation, interviews, and documentation during an international community service program. The results indicate that the KQM method significantly improved children's motivation and ability to memorize the Quran, with notable progress in memorization speed and understanding of verse meanings. Additionally, the method fostered a love for the Quran and introduced Indonesian national values through cultural activities such as national songs and traditional batik crafts. Key challenges included limited facilities and the children’s psychosocial conditions, requiring tailored teaching approaches. This study recommends the adoption of the KQM method by similar educational institutions and the development of international collaborations to expand its positive impact.